1989
DOI: 10.1063/1.343587
|View full text |Cite
|
Sign up to set email alerts
|

The formation of thin-film tungsten silicide annealed in ultrahigh vacuum

Abstract: Thin films of tungsten silicide have been formed by sputter depositing 710 Å of W metal onto (100)-oriented, 3–7 Ω cm, p-type silicon wafers. The samples were annealed in an ultrahigh vacuum ambient (pressure≤1.0×10−9 Torr) at temperatures ranging from 845 to 1100 °C for 30 s. The lack of oxygen contamination in the ambient allows the W-Si interaction to proceed, first producing both the W-rich W5 Si3 phase and the tetragonal WSi2 phase near 900 °C, followed by only the tetragonal, low-resistivity (30–40 μΩ cm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

1993
1993
2010
2010

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 12 publications
0
9
0
Order By: Relevance
“…At 700-750°C, the Cu 3 Si and CuTi 3 began to form on the surface. The results show that when the deposited W-Ti thin films were solid solution phase structure, the temperature of new compounds that appeared was slightly higher than that of the film with pure Ti and pure W. At the same time the W-Ti/Si interfacial reaction increased and small amounts of Cu began to diffuse into the Si substrates [16]. The films had a serious failure at 750°C, and when the annealing temperature was increased, the W-Ti thin films completely failed for Cu atoms totally changed into Cu 3 Si and CuTi 3 .…”
Section: Failure Mechanismmentioning
confidence: 78%
“…At 700-750°C, the Cu 3 Si and CuTi 3 began to form on the surface. The results show that when the deposited W-Ti thin films were solid solution phase structure, the temperature of new compounds that appeared was slightly higher than that of the film with pure Ti and pure W. At the same time the W-Ti/Si interfacial reaction increased and small amounts of Cu began to diffuse into the Si substrates [16]. The films had a serious failure at 750°C, and when the annealing temperature was increased, the W-Ti thin films completely failed for Cu atoms totally changed into Cu 3 Si and CuTi 3 .…”
Section: Failure Mechanismmentioning
confidence: 78%
“…Such voids can arise as a result of diffusion of Si atoms out of the Si substrate and into the W-Ti layer. Siegal et al have shown that in the case of annealed W-Ti/Si layers, Si moves into W, forming tungsten silicide [11,12]. The formation and evolution of the voids is described qualitatively in terms of mass transport of Si.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, it has also been used as structural material for MEMS devices such as pressure sensors (Fujimori et al 2007). WSi films have been prepared by many methods, for example, the reaction of a W thin film with Si at elevated temperatures (Siegal et al 1989), chemical vapor deposition (Pauleau et al 1989), deposition of W and Si by co-sputtering (Molarius et al 1991), or sputtering of WSi x (Washidzu et al 1991).…”
Section: Introductionmentioning
confidence: 99%